Toward a M2M-Based Internet of Vehicles Framework for Wireless Monitoring Applications - Fei Ding; Ruoyu Su; En Tong; Dengyin Zhang; Hongbo Zhu; Mohamed Wahab Mohamed Ismail (IEEE Access)
The Internet of Vehicles (IoV) has become an attractive research topic in the fields of communication networks and information processing due to its wide range of potential applications, including public transportation management, road traffic predication and control, environmental monitoring, and autonomous driving. Most research analyze the IoV’s data collected by dedicated machine-to-machine (M2M)-based platforms. Moreover, due to the lack of field experimental data, data transmission mechanisms from mobile vehicle terminals to the M2M-based platform rarely consider the proper transmission timing according to network performance and traffic conditions. To solve these problems, we propose an open M2M-based framework of wireless monitoring system for IoV. In the proposed framework, we design and implement a prototype of the mobile vehicle terminal. We also define the procedure of data transmission between the mobile vehicle terminal and the M2M-based platform. To prolong the lifetime of the mobile vehicle terminal, energy-efficient data transmission schemes for stopped and running vehicles are proposed, respectively, which reduce the unnecessary data transmission by jointly considering the variation of vehicle speed and received signal strength. We conduct a field experiment to verify the basic functions of the proposed M2M-based IoV monitoring system and the mobile vehicle terminal. Furthermore, the experimental results show that the proposed M2M-based platform with the mobile vehicle terminal enables customized and energy-efficient data delivery.